ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EKSPOR KOPI INDONESIA KE AMERIKA SERIKAT - I Ketut Sudiana, Tito Hilmi Yahya Pribadi (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
One of the natural resources owned by Indonesia is coffee, besides being sought after by the domestic community, it is also preferred by overseas groups. Coffee is one of Indonesia's export commodities. The purpose of this study is to find out how the influence simultaneously or partially between the amount of Indonesian coffee production, world coffee prices, and the exchange rate of the rupiah against Indonesian coffee exports to the United States. The analytical method used is multiple linear regression analysis, classical assumptions, simultaneous and partial analysis using SPSS version 2.5 application assistance, using secondary data. The results showed the variable amount of Indonesian coffee production, world coffee prices, and the exchange rate of the rupiah against the dollar simultaneously had a significant effect on Indonesia's coffee exports to the United States. In the partial test the number of production variables has a positive and significant effect, the variable world coffee prices have a negative and significant effect, the rupiah exchange rate variable against the dollar has a negative and significant effect on Indonesia's coffee exports to the United States Keywords: Indonesian coffee exports, total production, world coffee prices, the exchange rate of the rupiah against the dollar.